The Private Dining Restaurant: The Ideal Restaurant of the Future due to Covid-19? - Iva Slivar (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
This paper presents a model of a dislocated restaurant created based on dislocated hotels in Italy. This paper aims to provide an innovative solution for new initiatives in the food and beverage industry experiencing great losses due to the Covid 19 epidemic. The study uses an existing hotel model and adopts it in restaurants, and it uses analyses and synthesis for developing and defining new concepts. The private dining restaurant model represents a hybrid modification between dislocated hotels and classic al̀a carte restaurants and is more customized to the new normal. Depending on space constraints, a private dining restaurant can be built as a brand new restaurant or use the many empty spaces in the centre of many cities for this purpose, thus encouraging urban regeneration. Although, given its characteristics, this restaurant model is easier to apply from the beginning as such (as dislocated) rather than applying to existing buildings.
Keywords: L1; M16; Z3; 330; Covid 19; restaurant; privacy; social distancing; dislocated restaurant; innovation in tourism